The Validation of Theory of Planned Behaviour among Tax e- filers in Pakistan - Ullah, Hafiz Ahmed; Danish, Dr. Rizwan Qaiser; Ahmed, Dr. Ashfaq; Asad, Dr. Humaira; Baig, Waqas (The journal of contemporary issues in business and government, 2021)
In 2005, the Federal Board of Revenue (FBR), Government of Pakistan launched an e-tax filing portal to facilitate the tax filers to file their tax returns online. Submitting tax returns online is considered swift, easy, and economical. In this research study, we explain the tax filer’s intention to use the e-tax filing system through the theoretical lens of the Theory of Planned Behaviour after fifteen years of its implementation in Pakistan. Data was collected from 218 e-tax filing portal users located within the city of Lahore. The results show that subjective norm, attitude towards using e-tax filing portal and perceived behavioural control are associated with intention to use significantly. At present, the FBR is putting a lot of effort to increase the use of electronic filing systems, the outcomes of this study may facilitate the FBR to design a more effective plan to increase the electronic filing usage among Pakistani taxpayers. At the end of the article limitations and future instructions are given.